2010
DOI: 10.1590/s1807-59322010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Hospitalization among Children Ages Zero to Nine Years Old in the City of São Paulo, Brazil

Abstract: INTRODUCTION:The profile of child morbidity is an important parameter for defining and altering health policies. Studies about infant mortality are more numerous than those on morbidity, especially related to hospital admissions. The objective of this study is to describe the causes of admission in the public health system for children from zero to nine years of age in the city of São Paulo during the years 2002 to 2006 and compare these results to those from the national data.METHOD:Through a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
3
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 24 publications
4
21
3
9
Order By: Relevance
“…Other Brazilian studies 5,6,11,17 on hospitalization of children found lower hospitalization rates than in the current study. Castro et al 17 , using data from the PNAD 1998, showed an 11.1% hospitalization rate in children under one year and 6.9% from one to four years.…”
Section: Discussioncontrasting
confidence: 72%
See 4 more Smart Citations
“…Other Brazilian studies 5,6,11,17 on hospitalization of children found lower hospitalization rates than in the current study. Castro et al 17 , using data from the PNAD 1998, showed an 11.1% hospitalization rate in children under one year and 6.9% from one to four years.…”
Section: Discussioncontrasting
confidence: 72%
“…In PNAD 2008 6 , the hospitalization rate in children under four years of age was 8.4%. Ferrer et al 5 studied hospitalization of children from birth to nine years of age, from 2002 to 2006, in Brazil and in the city of São Paulo, and used data from the Brazilian Hospital Information System of the Brazilian Unified National Health System (SIH-SUS), showing a hospitalization rate of 17% in Brazil and 16% in São Paulo 5 . The National Demographic and Health Survey (PNDS 2006) 11 assessed the morbidity and mortality profile in children less than five years of age in Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations